AB1344-HPR POOLED ANALYSIS OF ASSOCIATION BETWEEN ABATACEPT OR OTHER TARGET DISEASE-MODIFYING ANTI-RHEUMATIC DRUGS (TDMARD) AND TYPE 2 DIABETES MELLITUS (T2DM)-RELATED HEALTHCARE RESOURCE UTILIZATION (HCRU) AND COSTS IN TNFI-NAÏVE RHEUMATOID ARTHRITIS (RA) PATIENTS WITH T2DM. (2nd June 2020) - Han, X.; Xia, Q.; Bao, Y.; Patel, V.; Roy, A.; Rajagopalan, V.; Lobo, F.
Abstract : Background: Limited information is available on the impact of target disease-modifying anti-rheumatic drugs (tDMARD) on patients with rheumatoid arthritis (RA) and type 2 diabetes mellitus (T2DM). Objectives: The objective was to compare T2DM-related healthcare resource utilization (HCRU) and cost for TNF inhibitors (TNFi)-naive patients pooled from two commercial databases with RA and T2DM receiving abatacept, other non-TNFi, or TNFi. Methods: A retrospective, observational study was conducted with MarketScan and PharMetrics (January 2008-September 2018). The study population included TNFi-naïve adult patients with RA and T2DM newly initiating abatacept, TNFi (adalimumab, certolizumab pegol, etanercept, golimumab, infliximab) or other non-TNFi (tocilizumab, anakinra, sarilumab, rituximab, tofacitinib). Date of tDMARD initiation was the index date. Patients had ≥2 RA diagnoses separated by ≥7 days, ≥1 T2DM diagnosis, and had ≥12 months of pre-index continuous enrollment. Follow-up ended at the end of patient insurance enrollment, study period or index treatment. T2DM-related HCRU and costs including inpatient stay, outpatient visits, ER visits, and pharmacy use were measured on a per-patient-per-month (PPPM) basis (2018 USD). Patients treated with abatacept were matched to TNFi and non-TNFi cohorts separately by propensity score adjusted with patients baseline comorbidities, HCRU, and costs. Results: A total of 16, 236 patients meeting criteria were identified. Most patients were female (74.3%), and the overall average age of 55.4 years (Table 1 ). After matching, 850 pairs of abatacept vs non-TNFi patients, and 1, 096 pairs of abatacept vs TNFi patients were included in the adjusted results. Patients initiating abatacept had 144 lower adjusted T2DM-related costs as compared to non-TNFi and 79 lower costs than TNFi cohorts (Table 2 ). Conclusion: TNFi-naive RA patients with T2DM newly initiating abatacept had lower adjusted rates of T2DM-related hospitalizations compared to patients who initiated a non-TNFi or a TNFi. Total costs were lower among patients initiating abatacept vs. patients who initiated a non-TNFi or a TNFi. Findings suggest that initial abatacept among TNFi-naïve patients may be able to reduce healthcare utilization arising from T2DM complications and reduce T2DM-related costs in RA patients. Disclosure of Interests: Xue Han Employee of: BMS, Qian Xia Shareholder of: I own shares of Bristol-Myers Squibb Company, Employee of: I am a paid employee of Bristol-Myers Squibb Company, Ying Bao Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, Vardhaman PATEL Employee of: Bristol Myers Squibb, Amrina Roy Employee of: Mu-Sigma, Varshini Rajagopalan Employee of: Mu-Sigma, Francis Lobo Shareholder of: Bristol-Myers Squibb (US), Employee of: Bristol-Myers Squibb (US)